Economic stagnation in emerging market countries: should this justify Keynes's law?. (9th August 2019) - Nikensari, Sri Indah; Santosa, Purbayu Budi; Sugiyanto, F.X.
This study aims to determine the aggregate demand factors that affect economic stagnation in middle-income emerging market countries, and whether Keynes's law can be a solution to solve the problem with increase demand. Using panel data from official sources such as the World Bank, several factors were tested to determine the effect on economic stagnation, at the 2010-2015 and 2010-2016 periods. By employing panel data modelling (with fixed effect model), the findings suggest that the decrease in household consumption, weak foreign investment, inefficient government spending and decreased export competitiveness have a significant positive effect on economic stagnation, while a low inflation rate has an insignificant effect on household consumption, as well as high lending interest rate have an insignificant effect on the decrease in the inflow of foreign direct investment. Therefore, Keynes's law must be applied appropriately by increasing aggregate demand to encourage declining economic growth through government interference.